2017
DOI: 10.21162/pakjas/17.2622
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological and Bacteriological Studies on Caseous Lymphadenitis in Small Ruminants

Abstract: Corynebacterium pseudotuberculosis is an intracellular bacterium, proliferates inside the macrophages, causes caseous lymphadenitis in small ruminants and is also responsible for human lymphadenitis. In current study, clinical signs and necropsy lesions suggestive of caseous lymphadenitis were observed in Chinkara deer (n=36), spotted deer (n=04) and Mouflen sheep (n=04) in a period of three years. Different pus samples were obtained from various superficial and internal lymph nodes, lungs, liver and spleen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…These results were in accordance with those obtained by Hatem et al [14] in Egypt and Hassan et al [18] in Saudi Arabia. In contrary, Abdel Wahab and Shigidi [19] reported that C. pseudotuberculosis isolates were highly sensitive to erythromycin and ampicillin.…”
Section: Discussionsupporting
confidence: 94%
“…These results were in accordance with those obtained by Hatem et al [14] in Egypt and Hassan et al [18] in Saudi Arabia. In contrary, Abdel Wahab and Shigidi [19] reported that C. pseudotuberculosis isolates were highly sensitive to erythromycin and ampicillin.…”
Section: Discussionsupporting
confidence: 94%
“…These organisms were previously reported as a cause of camel abscess by Wernery [6], Hassan et al . [7], Wernery [8], Berlin [11], and Wernery and Kinne [12]. The Gram-negative bacteria did not isolate alone in an abscess, but they were associated with Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…[5], Hassan et al . [7], Muckle and Gyles [32], Judson and Songer [33], Zhao et al . [34], and Mohan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corynebacterium pseudotuberculosis prevalence was reported to be 4.81% in a study conducted in Egypt (Mubarak et al 1999); other studies have reported a prevalence ranging from 0.2% to 90.07% (Al-Gaabary et al 2009). In addition, bacteriological studies have identified C. pseudotuberculosis at rates ranging from 1.1% to 32.6% (Al-Gaabary et al 2010;Hassan et al 2011;Zavoshti et al 2011). Isolation of C. pseudotuberculosis has also been reported as troublesome, depending on the infection stage of the disease, the immune status of the animal, and the presence of other bacterial species in the abscess content (Al-Gaabary et al 2009).…”
Section: Discussionmentioning
confidence: 99%